Recycling and utilization assessment of steel slag in metakaolin based geopolymer from steel slag by-product to green geopolymer. (25th October 2021) - Zhu, Xingyi; Li, Wenkai; Du, Zhao; Zhou, Siqi; Zhang, Yiyuan; Li, Feng
Highlights: Using orthogonal design to determine "optimum" ratios of different components (SiO2, Al2 O3, Na2 O, and H2 O) in a metakaolin based geopolymer. Based on the determined optimal ratio, the metakaolin is partially replaced with steel slag to synthetize the steel slag-metakaolin based geopolymer composite. The incorporation of steel slag contributes to the improvement of later strength (7 days and 28 days) of the steel slag-metakaolin based geopolymer composite. It is proved that the reason for the continuous strength increase promoted by steel slag is the continuous hydration reaction. Abstract: This paper presents an experimental study that aimed to recycle steel slag waste as a supplementary material in metakaolin based geopolymer, resulting in a new type of geopolymer composites. The mechanical properties and microstructure analysis of geopolymer composites were carried out. The metakaolin based geopolymer composite (MGC) was prepared by a three-key parameter (the mole ratios of SiO2 /Al2 O3, Na2 O/SiO2, and H2 O/Al2 O3 ) composition design method. The flexural strength and compressive strength test results show that the strength increment of MGC after 3 days is very limited. MGC exhibits the typical early strength property on compressive strength. Then, the steel slag powder (SS) was added to replace metakaolin to synthesize the steel slag-metakaolin based geopolymer composite (SSMGC) with the determined mix proportion. The strength test results indicate that the incorporation of SS contributes to the strength increment at a later age than MGC. The XRD patterns, SEM images, and EDS line scanning analysis indicate that SSMGC undergoes hydration in alkaline solution and accumulates hydrated calcium silicate gel with curing age besides the silica-alumina gel generated during geopolymerization. Due to the low content and low activity of steel slag active components, the degree of hydration and the amount of calcium silicate gel are inferior to the geopolymerization and silica-alumina gel caused by metakaolin, and ultimately lead to the relatively lower strength of SSMGC than that of MGC. However, the negative effect of adding SS to MGC on the mechanical strength becomes very small with curing age.